2022
DOI: 10.1155/2022/9673850
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Adverse Pregnancy Outcomes of Pregnant Women with Syphilis and Maternal-Infant Serological Association in Changzhou, China, 2015–2019

Abstract: Background. Although the prevention of mother-to-child transmission of syphilis program in China has achieved national coverage for 7 years, controversy still exists regarding the treatment of syphilis and the serological significance of syphilis. Objective. To explore the occurrence and influencing factors of adverse pregnancy outcomes among pregnant women with syphilis in Changzhou from 2015-2019 and to further analyze the impact of syphilis serologic titers on perinatal outcomes and neonatal serologic outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It should be noted that primary syphilis in males typically presents as a single, painless, Findings from the present study show that pregnant women with syphilis younger than 20 years or older than 35 years are more likely to have adverse pregnancy outcomes. Bai et al (37) observed that there is a statistical difference in age distribution between normal pregnancy outcomes and adverse pregnancy outcomes of gestational syphilis. The study of Dou et al (38) also showed that syphilis infected pregnant women younger than 20 years are more likely to have adverse pregnancy outcomes compared with those between 20 and 34 years old.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that primary syphilis in males typically presents as a single, painless, Findings from the present study show that pregnant women with syphilis younger than 20 years or older than 35 years are more likely to have adverse pregnancy outcomes. Bai et al (37) observed that there is a statistical difference in age distribution between normal pregnancy outcomes and adverse pregnancy outcomes of gestational syphilis. The study of Dou et al (38) also showed that syphilis infected pregnant women younger than 20 years are more likely to have adverse pregnancy outcomes compared with those between 20 and 34 years old.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%